The quality of banking and regional growth - Iftekhar Hasan; Michael Koetter; Michael Wedow (Deutsche Bundesbank, 2007)
We test whether output growth in European economic agglomeration regions depends on financial development. To this end we suggest a relative measure of the quality of financial institutions rather than the usual quantity proxy of financial development. In order to measure the quality of financial development we use profit efficiency derived from stochastic frontier analysis. We show that more efficient banks spur regional growth while the typically used quantity measure of financial development is negligible. Also, our results suggest an additional channel through which better banking can spur growth: the interaction of more credit with efficient banks.
Keywords: O47; O16; G21; O52; 330; Bank performance; regional growth; bank efficiency; Europe; Bank; Finanzdienstleistung; Technische Effizienz; Finanzintermediär; Regionales Wachstum; Schätzung; EU-Staaten